Tolerance to Ceftriaxone in Neisseria gonorrhoeae: Rapid Induction in WHO P Reference Strain and Detection in Clinical Isolates - Margaux Balduck; Jolein Gyonne Elise Laumen; Saïd Abdellati; Irith De Baetselier; Tessa de Block; Sheeba Santhini Manoharan-Basil; Chris Kenyon (MDPI AG, 2022)
In addition to antimicrobial resistance, bacteria contain other mechanisms to survive antibiotic exposure such as tolerance, defined as the ability to slow metabolism by the extension of the lag phase without altering antimicrobial susceptibility. In a number of bacterial species, tolerance has been associated with treatment failure and infection chronicity and is found to precede and facilitate antimicrobial resistance. It is unknown if tolerance can be induced in Neisseria gonorrhoeae. In this study, we determined if tolerance to ceftriaxone (CRO) can be induced in N. gonorrhoeae and detected in clinical isolates. To induce tolerance, WHO P N. gonorrhoeae reference strain samples were grown under daily 3 h intermittent CRO exposure (10× the MIC), partitioned by overnight growth in GC broth. This cyclic exposure was performed for 7 consecutive days in sextuplicate, with two control cultures to which GC medium without antibiotics was added. To detect tolerance and assess CRO susceptibility, modified Tolerance Disc (TD) and Epsilometer tests were performed on isolates after each CRO exposure cycle. Additionally, this experiment was carried out on 18 clinical N. gonorrhoeae isolates. Tolerance was first detected after two CRO exposure cycles in five out of six samples. The phenotype differed per cycle with no clear pattern. No tolerance was found in control samples but was detected in 10 out of 18 clinical isolates. The present study is the first to demonstrate the induction of tolerance to CRO in N. gonorrhoeae through antibiotic exposure. In addition, tolerance to CRO was found in clinical samples.